Analysis of Translation Techniques and Ideology in Olaf's Frozen Adventure Movie Subtitles - Siti Hunadah; Moh Kavin Lidinillah; Shalihah, Imra'atus (JELP Journal of English Language and Pedagogy, 2023)
This study aims to identify and analyze translation techniques and translation ideology used by translators in translating subtitle texts in the film Olaf's Frozen adventure. In this study using descriptive qualitative research with data in the form of words, phrases, clauses, sentences containing translation techniques in the subtitle text of the film Olaf's Frozen Adventure. The data collection technique in this study was to use documents and archives, by watching the film Olaf's Frozen Adventure and reading the available subtitles in both the source language and the target language and transcribing. In analyzing the data the steps taken by the researcher are watching and reading the subtitle text of the film Olaf's Frozen Adventure, analyzing translation techniques and translation ideology, and finally drawing conclusions. Based on the results of the analysis, there are 12 translation techniques used by translators in translating the subtitles of the film Olaf's Frozen Adventure from 133 data. Based on the frequency of use of these techniques are: reduction technique 17, borrowing 9, literal translation 27, equivalent 24, calculus 14, transposition 11, amplification 5, particulation 2, linguistic compression 17, modulation 5, adaptation 1, and generalization 1. applied by translators in translating the subtitles of the film Olaf's Frozen Adventure is the ideology of domestication.